Intravenous Immunoglobulin in Neonatal Sepsis - Li, Jiang; Gautam, Mahesh Kumar (Journal of Nepal Paediatric Society, 2013)
Neonatal sepsis remains the major cause of mortality and morbidity including neurodevelopmental impairment and prolonged hospital stay in newborn infants. Despite of advances in technology and optimal antibiotic treatment, incidence of neonatal sepsis and its complications remains unacceptably high especially in developing countries. Premature neonates in particular are at higher risk due to developmentally immature host defense mechanisms. Though not approved by Food and Drug Administration (FDA) U.S.A, off label use of intravenous immunoglobulin continues in many countries. Recent evidences showed no significant decrease in the mortality rate or other outcomes when intravenous immunoglobulin is administered in addition to standard therapies. Hence, use of intravenous immunoglobulin in suspected or proven neonatal sepsis is not recommended. The expense of prophylactic use of intravenous immunoglobulin administration for both term and preterm newborn population, given the minimal benefit is not justified. Future studies are required which should focus on other prophylactic or adjuvant treatment modalities in addition to the standard therapy in neonatal sepsis. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7400 J Nepal Paediatr Soc. 2013; 33(2):125-128